Hybrid drawing techniques : design process and presentation - Gorski, Gilbert (New York : Routledge, 2015)
'Learn to integrate traditional hand-drawing with digital techniques to expand your creative process. Hybrid Drawing has step-by-step demonstrations from a many different artists, architects, and students to show you how to exploit the strengths of each approach while compensating for any limitations. First you'll learn hand-sketching, perspective drawing, and the pros and cons of freehand drawings versus hardline, or computer, drawings. Next you'll cover the basics of creating drawings in CAD, 3D modeling software, and Photoshop, and learn methods to organize tools, store files, and print. After you've covered hybrid perspective drawings in-depth, advanced concepts, such as how to compose an image, how to use color, and how to include reflected light will give your drawings a professional polish. A companion website has copyright-free images for download, such as tonal patterns, watercolor fields, people, trees, and skies'--
Preface: Architecture in the Age of Digitalism -- Getting Started -- Traditional Drawing Techniques -- Perspective Drawing -- Digital Scanning Techniques -- Digital Coloring -- Hybrid Coloring Techniques -- Process: Hybrid Design Techniques -- Light and Shadow -- Composition Strategies -- Color Strategies
Includes bibliographical references and index.
Keywords: Architectural drawing -- Technique; Architectural drawing -- Data processing